2003
DOI: 10.1176/appi.ajp.160.9.1651
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled, Double-Blind Study of the Efficacy and Safety of Aripiprazole in Patients With Acute Bipolar Mania

Abstract: Aripiprazole had significantly greater efficacy than placebo for the treatment of bipolar disorder patients in acute manic or mixed episodes and was safe and well tolerated in this randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
238
1
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(275 citation statements)
references
References 31 publications
18
238
1
18
Order By: Relevance
“…21,22 In previous studies, aripiprazole was started at 30 mg/day, 6,7 whereas this study demonstrated the efficacy of aripiprazole with a treatment regimen starting at 15 mg/day. As 42% of aripiprazoletreated patients were on 15 mg/day at week 3, this study demonstrated that a treatment regimen with a starting dose of 15 mg/ day can be an effective approach for treating patients with acute bipolar mania.…”
Section: Discussionmentioning
confidence: 55%
“…21,22 In previous studies, aripiprazole was started at 30 mg/day, 6,7 whereas this study demonstrated the efficacy of aripiprazole with a treatment regimen starting at 15 mg/day. As 42% of aripiprazoletreated patients were on 15 mg/day at week 3, this study demonstrated that a treatment regimen with a starting dose of 15 mg/ day can be an effective approach for treating patients with acute bipolar mania.…”
Section: Discussionmentioning
confidence: 55%
“…This weight gain is in contrast to observations in studies with aripiprazole monotherapy in patients with schizophrenia, schizoaffective disorder, or bipolar disorder in which aripiprazole has been shown to have a low potential for weight gain. 16,[21][22][23][24][25][26][27][28][29] Furthermore, aripiprazole also demonstrated a low potential for weight gain when used as adjunctive treatment in patients with bipolar mania 29 or bipolar depression. 30 It is possible that concomitant prescription of aripiprazole with antidepressants may increase risk of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 20 articles were eligible for the current meta-analysis (Carlson et al, 2012;El-Mallakh et al, 2012;El Mallakh et al, 2010;Findling et al, 2013;Findling et al, 2009;Findling et al, 2012;Jeong et al, 2012;Kanba et al, 2014;Keck et al, 2007;Keck et al, 2003;Keck et al, 2009;Muzina et al, 2008;Quante et al, 2010;Sachs et al, 2006;Thase et al, 2008;Tramontina et al, 2009;Vieta et al, 2005;Vieta et al, 2008;Woo et al, 2011;Young et al, 2009) (Table 1). …”
Section: Study Selectionmentioning
confidence: 99%
“…One article (Keck et al, 2009) compared aripiprazole monotherapy and lithium in the acute phase of illness (aripiprazole = 155; lithium = 160), another article (El-Mallakh et al, 2012) compared aripiprazole monotherapy versus lithium in the maintenance stage (aripiprazole = 25; lithium = 38), and another article (Jeong et al, 2012) investigated the combination of aripiprazole with valproic acid versus haloperidol with valproic acid (aripiprazole = 28; haloperidol = 14). The remaining 15 articles (Carlson et al, 2012;El Mallakh et al, 2010;Findling et al, 2013;Findling et al, 2009;Findling et al, 2012;Kanba et al, 2014;Keck et al, 2007;Keck et al, 2003;Muzina et al, 2008;Quante et al, 2010;Sachs et al, 2006;Thase et al, 2008;Tramontina et al, 2009; A C C E P T E D M A N U S C R I P T …”
Section: Study Selectionmentioning
confidence: 99%